PRINCIPLES OF STRUCTURED SEARCH IN INFORMATION SEARCH SYSTEMS (Modern education and development, 2025)
Structured search plays a vital role in modern information retrieval systems, enabling efficient and precise access to relevant data. Unlike unstructured search, structured search utilizes predefined data models, indexing techniques, and query languages to optimize search performance. This paper explores the core principles of structured search, including metadata usage, database indexing, query optimization, and machine learning integration. It also discusses challenges such as scalability, relevance ranking, and multi-source data aggregation in search systems